دور السياسة المالية في توزيع وإعادة توزيع الدخل القومي في سورية - كنعان, علي; غانم, عدنان; إبراهيم, رشا يحيى (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتوافق النظام الضريبي كغيره من الأنظمة مع مختلف القوانين والتشريعات الاجتماعية والاقتصادية الموجودة في الدولة, ولكن بحكم الانفتاح على العالم الخارجي والعولمة حدث تغيّر في بعض الظروف الاجتماعية والاقتصادية, مما يتطلب منا تعديل النظام الضريبي ليتماشى مع هذه المتغيرات, لذلك يهدف هذا البحث إلى معرفة دور السياسة المالية في توزيع وإعادة توزيع الدخل القومي في سورية من خلال دراسة أثر النظام الضريبي والإنفاق العام في إعادة توزيع الدخل القومي, ومدى تأثير عملية إعادة توزيع الدخل القومي على معدلات النمو الاقتصادي في سورية, وانتهى البحث إلى النتائج التالية: 1- يساهم النظام الضريبي وبشكل سلبي في إعادة توزيع الدخل القومي, حيث أن الضريبة وباعتبارها أهم أدوات السياسة المالية لم تمارس الدور الواجب القيام به. 2- لم يحقق الإنفاق العام دوراً فعالاً في إعادة توزيع الدخل القومي لصالح الطبقات الفقيرة, بل على العكس تمّ إعادة توزيعه لصالح الطبقات الغنية. 3- تعد عملية إعادة توزيع الدخل القومي عاملاً أساسّياً في تحسين مستويات الادخار والاستثمار. 4- هناك علاقة طردية بين عملية إعادة توزيع الدخل القومي ومعدلات النمو الاقتصادي في سورية. The tax system like other systems matches with the different social and economic laws in the state, but due to the universality system, a change has occurred in some social and economical circumstances, which leads to matching the tax system with these changes, so the research aims at knowing the role of the financial policy in distributing and redistributing the national income in Syria through studying the impact of the tax system and the general spending in redistributing the national income, and the extent of affecting the redistributing process on the economical development rates in Syria. The research led to the following results: 1- The tax system contributes in redistributing the national income negatively, that is, the tax doesn't perform its real role, for tax is the most important financial policy. 2- The general spending doesn't achieve actual role in redistributing the national income for poor level, but it redistributes for rich level. 3- The redistribution of the national income process is considered a basic Factor in improving the levels of saving and investment. 4- There is a positive relation between the redistribution of the national income process and the rates of the economical development in Syria.